Peran Guru Akidah Akhlak dalam Menumbuhkan Nilai Karakter Tanggung Jawab Siswa Kelas Viii B di Madrasah Tsanawiyah Hidayatul Mubtadiin Jati Agung Kabupaten Lampung Selatan Tahun Pelajaran 2024/2025: Penelitian - Fadilah, Nisa Ul; Yasin, Muhammad; Anwar, Miftahul (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to describe: (1) The role of the Akidah Akhlak teacher in fostering the character value of responsibility among Grade VIII B students at Madrasah Tsanawiyah Hidayatul Mubtadiin Jati Agung; and (2) The supporting and inhibiting factors faced by the Akidah Akhlak teacher in developing students’ sense of responsibility. This research is a qualitative field study (field research) with a descriptive qualitative approach, which involves systematically, factually, and accurately describing situations and events. Data sources were obtained from both primary and secondary sources, with the primary data being key informants relevant to the research focus. Data collection techniques included observation, interviews, and documentation. To ensure data validity, triangulation was applied. The data analysis process involved data reduction, data presentation, and drawing conclusions. The findings of this study indicate that: (1) The role of the Akidah Akhlak teacher in instilling the character value of responsibility is reflected through the observation of three stages of classroom learning: planning, implementation, and evaluation. These stages were all carried out effectively by the Akidah Akhlak teacher at Madrasah Tsanawiyah Hidayatul Mubtadiin Jati Agung. Furthermore, disciplinary actions or sanctions given by the teacher varied depending on the students’ behavior, but were applied fairly without discrimination. Overall, the role of the teacher in promoting responsibility among students was considered to be quite effective.